Coconut shell-liquid smoke production based on the redistillation-filtration technology and its characterisation. Issue 1 (April 2020) - Putranto, A W; Oktaviani, A; Puspaningarum, F P; Sukardi,
Abstract: The utilization of coconut shell waste into liquid smoke has been carried out in recent years. However, the conventional technology that has been applied before only able to produce coconut shell-liquid smoke (CS-LS) in grade C. Whereas the further processing is needed to produce a higher quality of CS-LS into grade A. Hence, the aim of this study is to produce CS-LS based on the redistillation-filtration technology and analysed on its physical and chemical characterisation. The characteristic of CS-LS was analysed not only in physical parameters like yields, pH and density, but also identified of chemical compounds by using GC-MS method. The result showed that the redistillation and filtration technology produce CS-LS grade A and grade C was 2.17% and 0.83% respectively. The CS-LS grade A has pH and density value better than CS-LS grade C and inline with the SmokEz Enviro-23 standard. The CS-LS grade A was composed of 4 main chemical components such as phenolic, alkoxy, cycloacene, and furan compounds. While the CS-LS grade C was composed of 6 main chemical component such as phenolic, carbonyl, acid, alkoxy, ester and cycloalkene compounds. Although CS-LS grade C has more chemical compounds, CS-LS grade A has the highest phenolic compounds which is suitable to be produced commercially as a natural food preservative. Therefore, the application of redistillation-filtration technology in CS-LS production, potentially applied to SMEs or CS-LS industries in Indonesia.